Probiotic and Lifestyle Modification in Obese Pediatrics with Non-Alcoholic Fatty Liver Disease - Goyal, Pooja; Thapa, Babu Ram; Sharma, Neeta Raj; Bhatia, Anmol (Indian Journal of Community Health, 2019)
In the article, “Probiotic and Lifestyle Modification in Obese Pediatrics with Non-Alcoholic Fatty Liver Disease” [1] which appears in Volume 31, Issue 1 of Indian J Community Health, there is a correction in the disclosure of the name of the drug used in the article. At the time of the publication, we were not aware of any legal issues related to the product and the brand, otherwise we would have taken due care and would have mentioned about the “De Simone Formulation” in the article instead of the VSL#3 product. Also, the references we provided in the published article on the usage of VSL#3 in several indications should have been attributed to the De Simone Formulation. We used the original probiotic formulation (containing De Simone Formulation) in our study that was invented by Prof. Claudio De Simone,(2) and not the new VSL#3 which is a quite different product, as ruled by the US Federal Court. (3) This change does not affect the study of the paper. The authors would like to apologize for any inconvenience caused.